Opinion of the Farmers Regarding mobile based Agro-advisory Service - Harmandeep Kaur Sidhu and Lavleesh Garg, (Indian Journal of Extension Education, 2017)
Mobile based agro-advisories have been deployed by many organisations. the present study conducted in Jalandhardistrict of Punjab. It revealed that mobile assisted extension services led to higher degree of satisfaction about informationamong the farmers.